. Diagnostic value and therapeutic efficacy of serum levels of Pro-Gastrin-releasing peptide precursor (ProGRP) and neuron-specific enolase (NSE) small cell lung cancer: serum levels of Pro-Gastrin-releasing peptide precursor (ProGRP) and neuron-specific enolase (NSE - Wang, Ping (Journal of Medical Biochemistry, 2025)
Background: One of the most prevalent malignant tumors in China is primary lung cancer. This condition can be broadly categorized into two types: small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). SCLC is a type of neuroendocrine tumor highly malignant, undifferentiated, and prone to metastasis. In its early stages, SCLC typically does not present with noticeable symptoms. It is usually diagnosed when the disease has progressed to the middle or late stage. Therefore, early diagnosis is pivotal for enhancing the outcome of SCLC. Pro-Gastrin-releasing peptide precursor (ProGRP) and neuron-specific enolase (NSE) are tumor markers recommended by guidelines for SCLC. This study investigates the diagnostic value and efficacy of ProGRP and NSE serum levels in the context of SCLC, with the intention of providing more valuable references for SCLC diagnosis.Objective: The purpose of this research is to probe the diagnostic value and therapeutic efficacy of serum levels of ProGRP and NSE in SCLC, with the aim of enhancing the level of clinical diagnosis.Methods: A total of 84 SCLC patients who were admitted to our hospital from December 2022 to March 2024 were included in the SCLC group. The NSCLC group consisted of 45 patients diagnosed with NSCLC, while the benign lung disease group consisted of 57 patients diagnosed with non-cancerous lung conditions. Furthermore, the healthy control group comprised 60 healthy individuals. The serum levels of ProGRP and NSE were compared across all four groups. Moreover, the concentrations of ProGRP and NSE were compared between patients diagnosed with limited-stage and extensive-stage SCLC. The sensitivity and specificity of serum ProGRP and NSE levels for diagnosing SCLC were analyzed via ROC curve analysis. The critical value of the ROC curve was adopted as the grouping standard, and the clinical efficacy of different levels of serum ProGRP and NSE in SCLC patients was compared. Finally, the correlation between serum ProGRP and NSE levels and age, gender, smoking history, staging, distant metastasis, and tumor diameter in SCLC patients was evaluated.Results: The concentrations of serum ProGRP and NSE were observed in different groups. The findings confirmed that the SCLC group exhibited considerably elevated levels of serum ProGRP and NSE in comparison to the healthy control group, benign lung disease group, and NSCLC group, with the variance regarded as substantially significant (P
Keywords: small cell lung cancer; serum ProGRP; serum NSE; tumor marker; application value.